Storage stability and sensory quality of duhat (Syzyium cumini Linn.) Anthocyanins as a food colorant - Martinez, Sarah B.; delValle, Mercedita (1979)
The anthocyanin pigment of duhat fruits were extracted by the acidified ethanol extraction method. The extract was concentrated and added to a beverage system. The pH of the beverage was adjusted to three pH values. These beverages were stored at 12°C and 30°C in the dark and exposed to light at 30°C. Pigment stability decreased with increasing pH. Samples stored at 12°C had minimal pigment breakdown after 75 days of storage. All samples at 30°C had considerable pigment breakdown but the samples with pH 3.0 and 3.7 still showed acceptable color after 75 days. Samples exposed to light faded slightly but had absorbance values similar to the samples stored in the dark. Sensory evaluation tests showed that the anthocyanin extract had acceptable colorant properties but imparted a strong aftertaste which could not be masked by the artificial fruit flavor of the beverage.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coloring matter in food